Ogólnopolska konferencja naukowa „Współczesne problemy finansów i bankowości z perspektywy studentów, doktorantów i praktyków”: Polish National Conference „Contemporary problems of finance and banking from the perspective of students, graduate students and practitioners” - Rusak, Olga; Wawryniuk, Karolina (Management and Administration Journal, 2021)
x